Empowering Indonesian Da’wah Academy North Sumatera Students through AI-Driven Content Creation - Widyawati, Tri; Andriyani, Yunilda; Bin Nur, Taufiq; Bagus Sumantri, Imam; Tarisa Olivia; Muhammad Rozan Fawwaz Syariq; Septia Nugraha; Saddam Haikal; Rezka Zuhra Maulida (Talenta Publisher, 2024)
The rapid development of technology, especially in the field of artificial intelligence (AI), has created new opportunities for the creation of creative content and provided fresh approaches to captivate viewers and deliver important messages. The purpose of this community service project is utilizing AI technology to create preaching content for the students of the Indonesian Da'wah Academy located in North Sumatra. The activity is carried out in four stages, starting with a socialization of the activity plan to the partner and participants (students), followed by a presentation of training materials, independent learning, and task presentations. A number of AI-powered platforms are unveiled, including those for image, video and voice generation. The training emphasized the importance of digital literacy and ethical content creation within the context of dakwah (Islamic propagation). By the end of the program, a Student Content Creator Unit was established as a unit that will continue to enhance students' abilities in the digitalization of content. The evaluation was conducted in the form of a questionnaire, with results reflecting the enthusiasm and satisfaction of the participants regarding the training they attended. The program's success highlights the potential of AI in empowering students to enhance their creative skills while promoting positive and constructive narratives in the digital age.